The welfare gains from diversified environmental policies - Ben Blachly; Charles Sims; Travis Warziniack (Ecological Economics, 2026)

Texture engineering in cell-based seafood: Insights from structural and compositional benchmarks - Shaon Xin Ying Chuah; Karen M. Mancera Azamar; Tanmayee Kolli; Asli Z. Odabasi; Boce Zhang; Charles Sims; Renee Goodrich-Schneider; Ana M. Porras; Razieh Farzad (Food Research International, 2025)

3E + 3B: An Elaborated One Health Approach to Bridging the Researcher-Stakeholder Disconnect at the Food-energy-water Nexus Within Circular Bioeconomies - Ashley N. Morgan; Guangqing Chi; Erika R. Gavenus; Johana Husserl; Theodore B. Henry; Charles B. Sims; Debra L. Miller (Circular Economy and Sustainability, 2025)

Strategically timing land protection decisions to enhance biodiversity benefits - Paul R. Armsworth; Rachel E. Fovargue; Amanda A. Hyman; Gwenllian D. Iacona; Charles B. Sims; Hyun Seok Yoon (Conservation Biology, 2025)
Choices conservation organizations make when designing and implementing protected area strategies affect the timing of land protection. Well‐timed habitat protection will have a greater impact on biodiversity outcomes; yet, decisions affecting the timing of protection have received much less attention than other aspects of protected area design. We reviewed evidence on the timing of protected area establishment and on temporal variation in factors influencing the ecological effectiveness and cost‐effectiveness of establishing protected areas. Protected area coverage often increases in episodic bursts rather than at some uniform rate. Moreover, temporal variation in biodiversity indicators, habitat conversion threats, and the cost of protecting land suggests that the conservation benefit of protecting land at some times will be greater than that at others. Conservation organizations increase their flexibility to choose when they protect land by using flexibility‐creating mechanisms, such as loans, multiyear budgeting, and endowment management. Models and theory suggest how this can be done to have the largest positive impact for conservation by exploiting long‐ and short‐term variation in factors that affect the rate of biodiversity return on protected area investments.

Weather effects on natural surface trail use in an urban wilderness multi-use trail system - Douglas Gregory; Kristina Kintziger; Scott Crouter; Charles Sims; Matthew Kellogg; Eugene Fitzhugh (Journal of Outdoor Recreation and Tourism, 2024)

Ecosystem complementarities: Evidence from over 700 U.S. watersheds - Ben Blachly; Charles Sims; Travis Warziniack (Ecological Economics, 2024)

Air temperature spikes increase bacteria presence in drinking water wells downstream of hog lagoons - Jacob Hochard; Nino Abashidze; Ranjit Bawa; Randall Etheridge; Yuanhao Li; Ariane Peralta; Charles Sims; Tom Vogel (Science of The Total Environment, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Nitrogen Fertilizer Rate Affects Yield and Tuber Quality of Drip-Irrigated Tablestock Potatoes (Solanum tuberosum L.) Grown under Subtropical Conditions - Mildred N. Makani; Lincoln Zotarelli; Steven A. Sargent; Donald J. Huber; Charles A. Sims (American Journal of Potato Research, 2020)

Utilization of Descriptive Sensory Analysis and Volatile Analysis to Determine Quality Indicators of Aquacultured Whiteleg Shrimp ( Litopanaeus vannemei ) during Refrigerated Storage - Ying Fan; Asli Odabasi; Charles Sims; Keith Schneider; Zhifeng Gao; Paul Sarnoski (Journal of Aquatic Food Product Technology, 2020)

Fungal and herbivore elicitation of the novel maize sesquiterpenoid, zealexin A4, is attenuated by elevated CO2 - Shawn A. Christensen; Alisa Huffaker; James Sims; Charles T. Hunter; Anna Block; Martha M. Vaughan; Denis Willett; Maritza Romero; J. Erik Mylroie; W. Paul Williams; Eric A. Schmelz (Planta, 2018)

Bioeconomics of invasive species: using real options theory to integrate ecology, economics, and risk management - Charles Sims; David Finnoff; Jason F. Shogren (Food Security, 2016)

Effect of epiphyte infection on physical and chemical properties of carrageenan produced by Kappaphycus alvarezii Doty (Soliericeae, Gigartinales, Rhodophyta) - Charles S. Vairappan; Chong Sim Chung; Shigeki Matsunaga (Journal of Applied Phycology, 2014)

Room to move? Threatened shorebird habitat in the path of sea level rise—dynamic beaches, multiple users, and mixed ownership: a case study from Rhode Island, USA - Sally Ann Sims; Jennifer R. Seavey; Charles G. Curtin (Journal of Coastal Conservation, 2013)

Identification of Host Fruit Volatiles from Domestic Apple (Malus domestica), Native Black Hawthorn (Crataegus douglasii) and Introduced Ornamental Hawthorn (C. monogyna) Attractive to Rhagoletis pomonella Flies from the Western United States - Dong H. Cha; Wee L. Yee; Robert B. Goughnour; Sheina B. Sim; Thomas H. Q. Powell; Jeffrey L. Feder; Charles E. Linn (Journal of Chemical Ecology, 2012)

Distribution and symptoms of epiphyte infection in major carrageenophyte-producing farms - Charles S. Vairappan; Chong Sim Chung; A. Q. Hurtado; Flower E. Soya; Genevieve Bleicher Lhonneur; Alan Critchley (Journal of Applied Phycology, 2008)

Development of a catabolically significant genetic probe for polycyclic aromatic hydrocarbon-degrading Mycobacteria in soil - Kevin Hall; Charles D. Miller; Darwin L. Sorensen; Anne J. Anderson; Ronald C. Sims (Biodegradation, 2005)